Pemerkasaan pembangunan bangsa berasaskan acuan sendiri (Empowerment of race development based on their own mould) - Abdul Hamid, Solahuddin; Abdul Rahman, Mohd Nizho (2013)
Alternately colonialism over a long period was sup pressed, sorting and removing capabilities and the ability of the Malays in the current economy development. Colonial administration meddling in the government system has not developed economic development based on social justice as expected. Effects of discrimination for many years led to the Malays began to become discouraged, lose self confidence, low self-esteem that had spawned feeling that they are not able to do what other people should do. An undeniable fact, after the country gained independence, the Malays only gained political power shared other ethnic groups.Unfortunately, the same does not happen in the economic sphere, after various of development policies and social policies introduced by the government, their participation is still far behind compared to the other races until now.Thus, the redevelopment of the Malays economy need social engineering (change planned) with regard to culture and social structure system that suits with them that they should not continue to left behind the mainstream when the country achieved developed country.